The social sciences and development (Washington, D.C. : International Bank for Reconstruction and Development, 1974)
The papers in these volume were prepared as background materials for the participants in the conference. A summary of the discussions is included.
Papers presented at a conference in Bellagio, Italy, on the financing of social science research for development, February 12-16, 1974.
Includes bibliographical references.
rpm 25/01/2019
Loans
Keywords: Social sciences; Economic development